Target-specific deep brain stimulation of the ventral capsule/ ventral striatum for the treatment of neuropsychiatric disease - Zhang, Chencheng; Li, Dianyou; Jin, Haiyan; Zeljic, Kristina; Sun, Bomin (Annals of Translational Medicine; Vol 5, No 20 (October 20, 2017): Annals of Translational Medicine, 2017)
Deep brain stimulation (DBS) is a well-established therapy for Parkinson’s disease and other movement disorders. An accumulating body of evidence supports the extension of DBS application for the treatment of refractory psychiatric disorders. The ventral capsule/ventral striatum (VC/VS) is the most common anatomical target for obsessive-compulsive disorder (OCD), addiction, and depression. However, no specific electrode is available for the clinical targeting of these areas for DBS. According to the anatomical features of the VC/VS, a novel electrode was developed for simultaneous and independently programmed stimulation of the nucleus accumbens (NAc) and the anterior limb of the internal capsule (ALIC). This VC/VS-specific electrode has the potential to enhance stimulus intensity, provide independent and flexible target stimulation.